Hubungan antara Fear of Missing Out (FOMO) dengan Perilaku Phubbing pada Remaja Awal di SMP Negeri 3 Tasikmadu Karanganyar 2023/2024 - Farik Nur Rochim; Hera Heru Sri Suryanti; Eko Adi Putro (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This research aims to determine if there is a correlation between fear of missing out (FOMO) and binge eating behavior among young teenagers in SMP Negeri 3 Tasikmadu Karanganyar 2023/2024. This research was done in SMP Negeri 3 Tasikmadu Karanganyar. The subjects of this research were 60 students of classes VIII E and VIII B. This research is a quantitative correlative research. Data collection techniques use observation, interviews, questionnaires and documentation. Observation, interviews and questionnaire methods are the main methods used to obtain data on the fear of missing out and phubbing behavior. Meanwhile, the documentation method is a method extra In addition, the analysis techniques used are the normality test and the correlation test of moments and raw digital products. Based on the results of the data analysis regarding the relationship between the fear of missing out (FOMO) and bullying behavior among the adolescent youth of grade VIII of SMP Negeri 3 Tasikmadu Karanganyar in 2023/2024, it can be conclude that the results of the data analysis shows that the data get a calculated r value of 0.394. Then, the calculated r-value was seen with the product moment table of r with N = 60 and a significant level of 5% and 1%, 0.254 and 0.330, respectively. It turned out that the results of the data analysis obtained a higher r number. table size r or 0.254<0.394>0.330. In this regard, the null hypothesis or (Ho) that "There is no relationship between the fear of missing out (FOMO) and offensive behavior among young teenagers in SMP Negeri 3 Tasikmadu Karanganyar 2023 / 2024" is rejected and not proven. and the working hypothesis (Ha) that “there is a correlation between the fear of missing out (FOMO) and demanding behavior in adolescent youth SMP Negeri 3 Tasikmadu Karanganyar. 2023/2024", was found to be true at the 1% or 5% level of significance.